Comparing Late-line Treatment Sequence of Regorafenib and Reduced-intensity FOLFOXIRI for Refractory Metastatic Colorectal Cancer. (January 2020) - Tai, Cheng-Chun; Chen, Wei-Shone; Jiang, Jeng-Kai; Yang, Shung-Haur; Wang, Huann-Sheng; Chang, Shih-Ching; Lan, Yuan-Tzu; Lin, Chun-Chi; Lin, Hung-Hsin; Huang, Sheng-Chieh; Cheng, Hou-Hsuan; Chao, Yee; et al.
Abstract : Background: Both regorafenib and reduced-intensity FOLFOXIRI (riFOLFOXIRI) prolong survival in patients with metastatic colorectal cancer (mCRC). However, the sequence in which they should be administrated first in late-line treatment for refractory mCRC remains unclear. Patients and Methods: This study was a single-center retrospective cohort study that reviewed data from patients at Taipei Veterans General Hospital, Taiwan, with mCRC refractory to fluorouracil, irinotecan, oxaliplatin, cetuximab (wild-type RAS ), and bevacizumab. Patients were divided into 2 groups: a regorafenib-first group and a riFOLFOXIRI-first group. The Kaplan-Meier method and log-rank test were used to analyze survival, and a Cox proportional hazards model was used for univariate, multivariate, and subgroup analyses. Results: A total of 136 and 55 patients followed a regorafenib-first or riFOLFOXIRI-first treatment strategy, respectively. At baseline, patient characteristics were similar between the groups, except for younger age in the riFOLFOXIRI-first group. The regorafenib-first group had better overall survival (13.8 vs. 10.7 mo, P =0.038), whereas patients in the riFOLFOXIRI-first group had a better partial response rate ( P =0.005) but a higher rate of discontinuation due to adverse effects ( P =0.004) and cross-over to regorafenib ( P <0.001). Thus, no significant difference was observed in progression-free survival (regorafenib-first strategy: 3.17 mo; riFOLFOXIRI-first strategy: 4.97 mo; P =0.624). Regorafenib-first strategy, sex, and pathology were identified as independent prognostic factors. Subgroup analysis indicated that younger age, better performance status, stage IV disease, and mutant RAS gene favored the regorafenib-first strategy. Conclusion: Treatment with regorafenib-first followed by riFOLFOXIRI resulted in better overall survival when given as late-line treatment for patients with refractory mCRC.